Pengembangan Surfing Attraction di Pantai Sorake Kabupaten Nias Selatan - Bantors Sihombing; Jonda Melson Ge'e (Jurnal Ilmiah Akomodasi Agung, 2022)
Development is very important in a tourist attraction. In addition to being useful for the change and progress of the tourist attraction to increase tourist attraction, development can also increase the income of the local community. Sorake Beach tourism objects and attractions are also developing a surf attraction carried out with existing plans, To obtain data, interview informants directly to the field at the object and tourist attraction of Sorake Beach, South Nias Regency. By using field research, and library research, 15 people were interviewed directly, consisting of 4 surfers, 5 surfers club, 3 domestic visitors and 15 foreign visitors. Based on the results of the analysis, first, the potential of Sorake Beach in the development of surfing attractions has not been maximally developed either through promotion or beach conditions. Second, the facilities in the development of the surf attraction at Sorake Beach have not been fully equipped and several facilities are still not available at Sorake Beach, namely the surf store is a shop that provides various forms of surfing equipment (surfboards, surf clothes and other equipment) and surf repair. office is a business that provides surfboard repair services and also surfboard shapes. Third, the surf education center that should be in every surf spot is not yet available. Key Words: Surfing, Attraction, travel, objects and attractions